(untitled) (Journal of Global Accounting, 2023)
This study investigates the effect of leverage on earnings. This was motivated by the presumed paucity of recent literature in this regard, especially now that economic and environmental factors have left corporate organizations and stakeholders wondering what the ideal combination of debt should be. Hence, there is need to provide evidence on this decision area for more informed decisions in the future. This study thus, examined the effect of leverage ratios and debt-equity ratios on earnings per share of 15 manufacturing companies listed on Nigerian Exchange (NGX) Group. Ex-post facto research design was adopted and applied on data sourced from annual reports of the companies under study from 2012 to 2020 representing nine years period. Inferential statistics and multiple regression technique were adopted for the purpose of data analysis and hypothesis testing respectively. Results from this study showed that leverage ratios have positive effect on earnings per share while debt-equity ratios have negative effect on earnings per share. However, both effects were found not statistically significant at 5% significance level. The study thus, concludes that, financial leverage has no significant effect on shareholders’ earnings in Nigeria. it is recommended that total leverage management should be one of the focal points in business management for Nigerian manufacturing companies as there is positive effect of leverage on earnings per share. Even the insignificance of the effect may be moderated with good management emphasis on leverage management. Also, directors and managers of manufacturing companies in Nigeria are advised to employ effective and adequate debt policies to properly manage debts to enhance shareholders’ earnings.